MULTIMODAL STORYTELLING OF CENTRAL JAVANESE FOLKTALES FOR ENGLISH LEARNING IN PRIMARY SCHOOLS - Purnomo, Budi (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2026)
Integrating local culture into language learning creates meaningful and enjoyable experiences for young learners. This study investigates how Central Javanese folktales—such as Timun Mas, Roro Jonggrang, Bawang Merah & Bawang Putih, and Keong Emas—can support English reading and listening skills in primary schools while embedding moral values such as honesty, perseverance, and kindness. The research employed a classroom-based mixed-method design involving 60 fourth-grade students from two primary schools in Surakarta. The instructional intervention was implemented over eight weeks using multimodal storytelling materials that combined illustrated storybooks, audio narration, and interactive classroom activities. Data were collected through classroom observations, student performance assessments, and teacher interviews. Descriptive statistics were used to analyse students’ reading and listening performance, while thematic analysis was applied to interpret observational and interview data. Findings indicate that multimodal folktale-based instruction improves vocabulary acquisition, reading comprehension, and listening accuracy, while also encouraging active speaking through retelling, dramatization, and story discussion. Students additionally demonstrated higher motivation and enjoyment, connecting English learning with culturally familiar narratives and moral reflection. These results highlight the potential of culturally grounded multimodal storytelling as an engaging pedagogical approach for primary English education that integrates linguistic development, moral education, and student-centred learning.